The last sprint - Abd Razak, Dzulkifli (2010)
IF we are on a Wawasan 2020 100-metre sprint, we have just entered the last 30 metres of the race. We should have gained enough momentum by now to dash forward with much confidence to win. We can almost hear the cheers on the sidelines to ensure that we are kept motivated and focused. There is no obstacle that could stop us from achieving that one mission we have set for ourselves. Yes, we have less than a decade to make it a reality.